Design and Build Automatic Rice Winnowing and Weighing Equipment IoT (Internet of Things) Based - Siwi Andriani; Abdul Rakhman; Suroso Suroso (Jurnal Ecotipe (Electronic, Control, Telecommunication, Information, and Power Engineering), 2022)
Technological developments are growing rapidly without exception in the agricultural sector. Food needs are increasing every year in Indonesia, rice is a staple food for most Indonesian people before being distributed, it is necessary to process rice including cleaning and weighing so that it can reach the hands of buyers. This research was conducted using the R&D (Research and Development) method with a prototype development model. development procedures include the stages of needs analysis, system design and design, prototyping, testing and validation. The design of this rice winnowing and weighing device uses the telegram application, Arduino ide which is connected to the internet as software and hardware NodeMCU ESP 8266, Arduino Uno as a controller, hx711 load cell sensor as a weighing sensor, power supply as a power supplier, relay module, LCD 16 x 20, buzzer, MG996 servo motor, and AC fan that can be controlled remotely using IoT (Internet of Things).